Reformas educacionais e as ciências humanas: representações sociais de professores de história e geografia - Assis, Cristiane Sousa de (2023)
Neoliberal policies and the redefinition of the State's role, amidst disputes with major private groups and under the growing influence of conservative agendas, have promoted a hierarchization of knowledge, reflected in the High School Education Reform and the National Common Curricular Base. Influenced by the conservative agenda and in conflict with major private groups, these policies have direct consequences for the devaluation of public education and humanities disciplines. The objective of this researc h is to analyze the social representation of six History and Geography teachers who teach at the 7th and 8th grades of the municipal public school network in João Pessoa, regarding this reform and how these modifications are redefining the place of the Humanities in the current educational context. This is qualitative research , inspired by an ethnographic approach, grounded in the interpretative and processual framework of social representations and content analysis. Methodological procedures included semi structured interviews and the use of techniques such as Dialogical Conversation Circles and Free Word Association. The results indicate that the teachers view the reform as a political arrangement to discredit public education, undermine the work of educat ors, and direct the formation of young people towards the job market. The proposal for curricular integration, closely related to issues of regulation, imposition, homogenization, and social control, is seen by the teachers as a significant setback. The em phasis placed on mastering basic skills in Portuguese and Mathematics is perceived as an intentional process that privileges certain areas of knowledge at the expense of others, resulting in a reduction in the scope of humanities disciplines in basic education.